The Influence of The endoparasitoid Apanteles (Cotesia) Glomerata L (Hymenoptera: Braconidae) On Growth, Food Consumption, Of Its Host Larva, Pieris Brassicae L (Lepidoptera: Pieridae) Under Laboratory Condition - بدور زينه; علي رمضان; إياد محمد (Latakia University Journal -Biological Sciences Series, 2023)
The results of the laboratory study showed that the C. glomerata has a direct and significant effect on growth and development of larval stage of P. brassica under laboratory conditions, where parasitization caused a clear increase in the duration of the larval stage compared to the unparasitised one, where the average of the duration in the fifth larva with parasitization for 48 hour was 6.96±0.73 day comparing to control 4.52±0.96 day, in addition to a significant increase in the weight of the parasitized larva at the third age to the last one. The average of weight with parasitiztion for 48 hour in the third larva was 42.31±16.4 mg comparing with 29.92±3.07 mg in the control. Food consumption and food utilization data were higher when the larva was exposed to the parasitoid for 48 hours, which was confirmed by the clear and significant differences in the studied nutritional index between uninfected larva and parasitized larva under laboratory conditions.